InteractomeSeq: a web server for the identification and profiling of domains and epitopes from phage display and next generation sequencing data. Issue Volume 48:Issue W1(2020) (13th May 2020) - Puccio, Simone; Grillo, Giorgio; Consiglio, Arianna; Soluri, Maria Felicia; Sblattero, Daniele; Cotella, Diego; Santoro, Claudio; Liuni, Sabino; Bellis, Gianluca De; Lugli, Enrico; Peano, Clelia; Licciulli, Flavio
Abstract: High-Throughput Sequencing technologies are transforming many research fields, including the analysis of phage display libraries. The phage display technology coupled with deep sequencing was introduced more than a decade ago and holds the potential to circumvent the traditional laborious picking and testing of individual phage rescued clones. However, from a bioinformatics point of view, the analysis of this kind of data was always performed by adapting tools designed for other purposes, thus not considering the noise background typical of the 'interactome sequencing' approach and the heterogeneity of the data. InteractomeSeq is a web server allowing data analysis of protein domains ('domainome') or epitopes ('epitome') from either Eukaryotic or Prokaryotic genomic phage libraries generated and selected by following an Interactome sequencing approach. InteractomeSeq allows users to upload raw sequencing data and to obtain an accurate characterization of domainome/epitome profiles after setting the parameters required to tune the analysis. The release of this tool is relevant for the scientific and clinical community, because InteractomeSeq will fill an existing gap in the field of large-scale biomarkers profiling, reverse vaccinology, and structural/functional studies, thus contributing essential information for gene annotation or antigen identification. InteractomeSeq is freely available at https://InteractomeSeq.ba.itb.cnr.it/